2018
DOI: 10.1038/s41598-018-30525-3
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells as targets for DC-based immunotherapy of colorectal cancer

Abstract: The therapy of colorectal cancer (CRC) patients is often unsuccessful because of the presence of cancer stem cells (CSCs) resistant to conventional approaches. Dendritic cells (DC)-based protocols are believed to effectively supplement CRC therapy. Our study was aimed to assess how the number and properties of CSCs isolated from tumor tissue of CRC patients will affect the biological characteristics of in vitro modified DCs. Similar procedures were conducted with the using of CRC HCT116 and HT29 cell lines. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 91 publications
0
30
0
Order By: Relevance
“…Solid tumors grow in a three-dimensional (3D) spatial conformation, resulting in heterogeneous exposure to oxygen and nutrients, as well as to physical and chemical stresses, which is not mirrored in the 2D adherent systems of cancer cell cultures (43). It has been suggested that spherical cultures better mimic the cancer cell organization and development in vivo (10,12,44). Similar to solid tumors, the external layer of a sphere is composed of cells displaying high proliferation rates, the middle layer is essentially formed by senescent cells, and the core contains necrotic cells (11).…”
Section: Discussionmentioning
confidence: 99%
“…Solid tumors grow in a three-dimensional (3D) spatial conformation, resulting in heterogeneous exposure to oxygen and nutrients, as well as to physical and chemical stresses, which is not mirrored in the 2D adherent systems of cancer cell cultures (43). It has been suggested that spherical cultures better mimic the cancer cell organization and development in vivo (10,12,44). Similar to solid tumors, the external layer of a sphere is composed of cells displaying high proliferation rates, the middle layer is essentially formed by senescent cells, and the core contains necrotic cells (11).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using CD133 positive, CD29 positive and CD44 positive CSCs showed that the number of activated DCs was decreased after CSC lysate/LPS (intracellular) or CSC conditioned medium/LPS (extracellular) stimulation. This result suggested that CSCs might impair the functions of DCs [49]. Although the relationship between DCs and GCSCs is still unclear, the functional DCs are required in the immune microenvironment for T cell activation.…”
Section: Gcscs and The Immune Microenvironmentmentioning
confidence: 96%
“…Bruttel and Wischhusen on the other hand showed that CSCs evade the immune system via lack of molecules needed for T cell recognition [ 390 ]. Several other studies showed that CSCs evade the immune system due to their creation of an immune suppressive microenvironment [ 391 , 392 ]. Despite the above, the high expression of PD-L1 on the CSCs’s surfaces makes CSCs targets of checkpoint inhibitors.…”
Section: Targeting Cancer Stem Cells In Tumor Microenvironmentmentioning
confidence: 99%